2015
DOI: 10.1111/wrr.12329
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of critical limb ischemia: Major vs. minor amputation comparison

Abstract: Healthcare providers treating wounds have difficulties assessing the prognosis of patients with critical limb ischemia who had been discharged after complete healing of major amputation wounds. The word "major" in "major amputation" gives the impression of "being more severe" than "minor amputation." Therefore, even if wounds are healed after major amputation, they imagine that prognosis after major amputation would be poorer than that after minor amputation. We investigated the prognosis of diabetic nephropat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Furthermore, whether the surgical procedure of minor LEA was too conservative in some severe cases who should have had a higher level of amputation was not known. Our findings again stress the point that the coronary artery disease [22] and renal function [18] are associated with mortality in diabetic patients after lower extremity amputations.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Furthermore, whether the surgical procedure of minor LEA was too conservative in some severe cases who should have had a higher level of amputation was not known. Our findings again stress the point that the coronary artery disease [22] and renal function [18] are associated with mortality in diabetic patients after lower extremity amputations.…”
Section: Discussionsupporting
confidence: 72%
“…However, the study from Taiwan found that major amputation is not an associated risk factor for mortality after adjusting for sex and age [21]. Another study demonstrated that there is no difference in prognosis between major and minor amputations at two years if the surgical wounds could heal [22]. In our study, wounds healed after amputations among most patients, which might explain that the level of amputation was not associated with mortality.…”
Section: Discussionmentioning
confidence: 50%
“…Some have studied the NPWT in amputations and proved that patients who underwent amputation and who had negative pressure wound therapy had less major amputation than patients with conventional dressing [12]. However, Mendonca et al, has reported that patients with severe peripheral vascular disease should be treated by other methods because of high failure rate [13]. Which was the case of three of our patients who underwent another amputation.…”
Section: Discussionmentioning
confidence: 66%
“…Only patients with below-knee or more distal-level amputation were included in this study, as above-knee amputation (AKA) is not performed under PNB alone in our institution. Below-knee amputation (BKA) was regarded as a major amputation, whereas a more distal-level amputation was regarded as a minor amputation [ 14 , 15 , 16 , 17 ]. Amputation of the forefoot, midfoot, and hindfoot were considered minor.…”
Section: Methodsmentioning
confidence: 99%